Empowering Women through Artificial Intelligence: Opportunities and Challenges - Marzia Ebrahimi; Behnaz Rahimi; Manizha Sharifi; Diba Sadat; Nahid Amiri; Sadaf Khalil; Tamanna Quraishi (Journal Electrical and Computer Experiences, 2024)
This study investigates the impact of artificial intelligence (AI) on women’s empowerment, addressing the pressing problem of gender inequality in various sectors. With the rapid advancement of AI technologies, understanding their role in enhancing women's access to education, safety, and leadership opportunities has become essential. The primary purpose of this research is to explore the perceptions of female students at an online women’s university regarding AI's potential benefits and challenges in promoting empowerment. Employing a quantitative research methodology, a structured questionnaire was distributed to 160 female participants across various faculties. The data collected were analyzed using descriptive and inferential statistical techniques, revealing significant insights into the participants' attitudes towards AI. The results indicate a generally positive perception of AI, with many participants recognizing its potential to improve educational opportunities, enhance online safety, and support women's leadership in technology. However, there are notable concerns regarding the accessibility and implementation of AI, suggesting the existence of barriers that may hinder its effectiveness. In conclusion, this study underscores the importance of addressing these barriers to maximize AI’s benefits for women. By fostering an inclusive approach to AI development and deployment, stakeholders can create an environment that empowers women, thereby contributing to the overall goal of gender equality in the digital age.